Using theoretical frameworks to analyze democratic student–teacher engagement and autonomous learning for academic achievement in Zimbabwe - Magwa, Logic; Mohangi, Kamleshie (Frontiers in Education, 2022)
Positive student-teacher engagement that fosters independent learning is the fulcrum for academic success. The purpose of this paper is to investigate stakeholder opinions on the intrinsic importance of a democratic student-teacher relationship and autonomous learning in mediating students' academic progress in Zimbabwean secondary schools. This case study's qualitative data was gathered through interviews and focus groups. To frame our understandings, we used Foucault's theory of power relations and the self-determination theory of motivation. The 40 participants were general teachers (n = 12), guidance and counseling teachers (n = 2), educational psychologists (n = 2), and students (n = 24), selected through purposive sampling techniques. The data was analysed using the thematic content analysis approach. Findings revealed participants’ perceptions that democratic student-teacher relationships and autonomous learning opportunities may serve as a panacea to improve students’ participation, motivation, and overall academic performance. The study recommends that we provide extensive training to teachers regarding policies, directives, and public acts that inform and educate on enhancing student-teacher relationships in a democratic manner that fosters autonomous learning in schools. Future longitudinal studies could investigate the long-term effects of positive student-teacher engagement and teacher-supported autonomous learning on student academic achievement.